Videogames and logical mathematical ability: the Game-Over project - Liliana D'Angelo (Formare, 2017)
Focus of this paper is the possibility to broaden the learning experience by using videogames to promote a “learning by doing” methodology.Purpose of the “Game-Over” project was in fact giving, through designing and implementation of a videogame, valuable educational experiences simulating interactive learning scenarios, aiming to improve students’ problem solving skills.